CONTROLE DA ACIDEZ DO SOLO EM SISTEMAS DE PRODUÇÃO DE AZEVÉM ANUAL E MILHO SILAGEM: ESTUDO EM MÉDIO PRAZO - Santos, Jéssica Alves dos (2015)
The liming is essential for building soil fertility, enabling exploitation more sustainable of production systems. However, the efficiency and the residual effect of lime used are dependent on the degree of soil disturbance, which has been distinguished in conservation production systems. The objectives of this work are (i) quantify the yields of dry matter (DM) and content crude protein (CP) in maize silage during the years 2008-2014; and (ii) evaluate the changes in soil fertility attributes: active acidity (pH), potential acidity (H+Al), exchangeable acidity (Al3+) and base saturation (V) 24 and 60 months after of liming, in different methods tillage and uses of annual ryegrass during the autumn-winter. The experiment was conducted in Castro (PR) in an Oxisol dystrophic clayey. The design experimental was a randomized complete block design with split plots and four replications. In the plots were studied four methods of soil tillage: conventional tillage (CT), minimum tillage (MT), no-tillage (NT) and chiseled no-tillage (CNT). In the subplots were studied three purposes of use of annual ryegrass: cover crop (CC), silage (S) and grazing of the dairy heifers in integrated crop-livestock (ICL). In medium-term, the tillage methods (CT, MT, NT, and CNT) do not influence the yield of DM and CP content of maize silage. The uses annual ryegrass for S and ICL not influence yield of DM and provide high CP in corn silage. Using the preceding crop just as CC provides least amount of benefits systems to annual ryegrass production and maize silage. Lower acidity and higher V were observed in layer the 0-5 cm in NT. Compared to the NT, the CNT not improve the acidity and V. The annual ryegrass for the S and ICL provided, over time, decrease in the acidity of the soil in layers below 10 cm depth. The NT combined with ICL provides improvement in soil acidity conditions after 60 months after liming.